Effect of various factors on pull out strength of pedicle screw in normal and osteoporotic cancellous bone models. (February 2017) - Varghese, Vicky; Saravana Kumar, Gurunathan; Krishnan, Venkatesh
Highlights: Currently individual factor effect of density, insertion depth and insertion angle has been widely studied in literature. Our study finds if the interaction effect between factors has any significant contribution. Interaction between factors has significant effect on pull out strength of pedicle screw. Density contributes highest toward pull out strength and insertion torque of pedicle screw. Insertion angle has no significant effect on insertion torque of pedicle screw. There is no significant correlation between insertion torque and pull out strength in case of extremely osteoporotic bone model. Abstract: Pedicle screws are widely used for the treatment of spinal instability by spine fusion. Screw loosening is a major problem of spine fusion, contributing to delayed patient recovery. The present study aimed to understand the factor and interaction effects of density, insertion depth and insertion angle on pedicle screw pull out strength and insertion torque. A pull out study was carried out on rigid polyurethane foam blocks representing osteoporotic to normal bone densities according to the ASTM-1839 standard. It was found that density contributes most to pullout strength and insertion torque. The interaction effect is significant ( p < 0.05) and contributes 8% to pull out strength. Axial pullout strength was 34% lower than angled pull out strength in the osteoporotic bone model. Insertion angle had no significant effect ( p > 0.05) on insertion torque. Pullout strength and insertion torque had no significant correlation ( p > 0.05) in the case of the extremely osteoporotic bone model.